Opera and Censorship in 20th Century Slovakia - Števuliak, Ján (Taideyliopiston Sibelius-Akatemia, 2024)
This thesis examines the development of Slovak language opera in Czechoslovakia between 1948 and 1989, focusing on the societal significance and the role of censorship in shaping these works. Through case studies of Svätopluk (1960) by Eugen Suchoň and Vzkriesenie (1962) by Ján Cikker, this research explores how Slovak composers navigated the political and cultural climate of post-World War II Czechoslovakia under Communist rule. Drawing on Marxist, Foucauldian and Bourdieusian frameworks of culture and power, alongside the New Censorship theory, this thesis challenges traditional views of censorship as merely repressive and offers a nuanced understanding of how state control over artistic expression influenced creative decisions. By analysing composers’ responses to the pressures of nationalism, prescribed social realism, and Soviet-style cultural policies, this study sheds light on the complexities of cultural production in a totalitarian context. The findings contribute to broader discussions on the intersection of art, politics, and power, particularly in the context of Slovak music history, which has been less explored in comparison to Czech musical traditions. Ultimately, this work offers new insights into the agency of composers in a politically charged artistic landscape. keywords: opera, Slovakia, Czechoslovakia, censorship, modernism, nationalism, socialist realism, Suchoň, Cikker, Krútňava, Svätopluk, Mister Scrooge, Vzkriesenie
Keywords: sensuuri; musiikki; oopperataide; Tšekkoslovakia; Slovakia; oopperat; musiikinhistoria; kulttuuripolitiikka; kulttuuri; fi=sävellys ja musiikinteoria|sv=komposition och musikteori|en=Composition and Music Theory|